1979
DOI: 10.1029/ja084ia09p05361
|View full text |Cite
|
Sign up to set email alerts
|

The solar modulation of cosmic ray electrons 1969–1977

Abstract: We discuss the gross morphological features of the cosmic ray electron spectrum from 200 MeV to 6 GeV as measured in eight of the nine years 1969–1977. We find no evidence that the solar magnetic field polarity change of 1970–1971 affected the relative modulation of electrons and protons. However, previously noted problems in explaining the variation of both the electron and proton modulation by one model can at least qualitatively be understood by allowing simultaneous variations in the diffusion coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Hence, in Figure 1 we show the electron spectra obtained from our flights in 1987, 1990, 1992, and 1994. These data have been reduced and corrected according to our standard procedure [Schmidt, 1972;Fulks, 1975;Evenson et al, 1979;Tuska, 1990]. The fluxes reported in Figure 1 are consistent with partial results reported for the flights in 1987 [Tuska, 1990] and 1990 Evenson et al, 1991].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hence, in Figure 1 we show the electron spectra obtained from our flights in 1987, 1990, 1992, and 1994. These data have been reduced and corrected according to our standard procedure [Schmidt, 1972;Fulks, 1975;Evenson et al, 1979;Tuska, 1990]. The fluxes reported in Figure 1 are consistent with partial results reported for the flights in 1987 [Tuska, 1990] and 1990 Evenson et al, 1991].…”
Section: Introductionsupporting
confidence: 74%
“…A unique series of balloon observations of cosmic electrons begun in 1968 at the University of Chicago [Hovestadt et al, 1970] has been continued since 1984 by the Bartol Research Institute using the same instrument. Data from this instrument have been used over a large energy range to study solar modulation of electrons during the time period 1968-1987 [Schmidt, 1972;Fulks, 1975;Evenson et al, 1979Evenson et al, , 1983Evenson and Meyer, 1984;Garcia-Munoz et al, 1986, 1987, 1990Tuska, 1990;Tuska et al, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…Korff [1977, 1979] proposed that the charge sign difference was the cause of the difference in the modulation of protons and electrons. Evenson et al [1979a] studied the simultaneous modulation of protons and electrons through the 1970 solar maximum in a common rigidity interval around 0.4 GV., without finding a correlation between the time variations of the ratio electron/proton and the polarity change of the interplanetary magnetic field. Evenson and Meyer [1984] analyzed proton and electron measurements carried out after the 1980 change in polarity of the polar solar magnetic fields and showed that after the 1981 minimum in cosmic ray intensity • Also at Department of Physics, University of Chicago, Illinois.…”
Section: Introductionmentioning
confidence: 99%
“…Even the added leverage afforded by the difference in drift velocity between electrons and protons has failed to resolve this important issue. Although the hysteresis curves in the ratio of electrons to protons between the 1968 and 1980 maxima of solar activity appear quite divergent, differences in the temporal structure of the two maxima rather than sensitivity to the polarity of the heliospheric field could well be the dominant factor [Evenson et al, 1979;Evenson and Meyer, 1984].…”
Section: Introductionmentioning
confidence: 99%